Assessment and Restoration of an Earthquake-Damaged Historical Masonry Building - Maraveas, Chrysanthos (Frontiers in Built Environment, 2019)
This paper presents an assessment of the capacity and enhancement of the seismic performance of a historical masonry structure in Plomari, a town on the south coast of Lesbos island in Greece. Owing to uncertainties regarding the properties of the material and the effectiveness of the members in providing lateral resistance, the study was particularly challenging. In addition, the fact that the structure consisted of a variety of structural element types, e.g., unreinforced masonry from natural stones, timber-framed masonry (with burned clay masonry units) and timber girders, while lacking horizontal diaphragms, introduced complexities to the response of the structure in both directions. In the design of the retrofit, the need to preserve the building’s architectural and historical value by minimizing interventions posed several problems. To solve them, conventional as well as state-of-the-art strengthening methods are proposed. Moreover, the procedures of these methods are in accordance with the Greek seismic design code of 1959 and European standards (Eurocodes) related to earthquake-resistant masonry as well as guidelines for the design of timber and reinforced concrete. Seismic analyses of the structure were carried out with two different methods (statically applied load and time history analysis) for comparison. The results verify the improvement in its behavior in response to earthquakes as a result of the proposed strengthening methods.